Exceptional creep resistance of a directionally solidified superalloy: temperature-dependent evolution of microstructure and dislocations - Yunpeng Fan; Xinbao Zhao; Yu Zhou; Yuan Cheng; Shuli Zeng; Quanzhao Yue; Wanshun Xia; Yuefeng Gu; Ze Zhang (Materials Research Letters)
This study systematically analyzed the microstructure, grain boundary, and dislocation evolution of a novel directionally solidified superalloy with excellent creep resistance under different conditions and the alloy outperformed first-generation single-crystal superalloys in creep resistance. Experimental results revealed that higher temperatures inhibited the broadening of grain boundary serrations while reducing the degree of topological inversion and delaying the widening of γ channels. Dislocation behavior analysis showed that lower temperature promoted the formation of a superdislocation network, which effectively pinned the motion of superdislocations, reducing the creep rate during the secondary creep stage and delaying the transition to tertiary creep.